EVOLUTION OF CARDIOLOGY AS A SPECIALTY - Edo Tondas, Alexander; Anwar, Chairil; Agustian, Rolando (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Science is a conscious effort to try, find and improve human understanding from various aspects in human nature. The number of medical specialties continues to grow until they reach even smaller branches known as sub-specialties. One type of specialization in medical science is the specialization of cardiology, the science that focuses on the needs of the heart organ. The development of cardiology cannot be separated from the history behind it. The progress of cardiology up to this point is a continuous interrelated journey. Every lesson in the past will be a capital for future experience, as will cardiology, where each phase becomes the foundation for future development.